2006
DOI: 10.1055/s-2006-931585
|View full text |Cite
|
Sign up to set email alerts
|

Hypericum perforatum: Which Constituents may Induce Intestinal MDR1 and CYP3A4 mRNA Expression?

Abstract: In vitro and in vivo studies suggest that extracts of St John's wort (Hypericum perforatum, L .; SJWE) interact with various drugs, by enhancing their elimination, due to induction of intestinal and hepatic cytochrome P450 3A4 (CYP3A4) and P-glycoprotein (P-gp), the gene product of multidrug resistance gene 1 (MDR1/ABCB1). The aim of our study was to identify the major constituents responsible for this induction and their relative importance. Therefore, plant extracts were investigated that vary in these const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…This is in contrast to other substrates of P-gp such as dexamethasone and ritonavir (Gutmann et al, 2006;Narang et al, 2008;Perloff et al, 2004).…”
Section: And R-citalopram and Its Metabolites In Abcb1ab (-/-) Knocmentioning
confidence: 73%
“…This is in contrast to other substrates of P-gp such as dexamethasone and ritonavir (Gutmann et al, 2006;Narang et al, 2008;Perloff et al, 2004).…”
Section: And R-citalopram and Its Metabolites In Abcb1ab (-/-) Knocmentioning
confidence: 73%
“…St John's Wort may alter the expression of various membrane pumps and result in decreased bioavailability of a variety of drugs. Hypericin at a concentration of 10 mM induced mRNA expression of the Pgp gene MRD1 in the human colorectal carcinoma line LS180 (Gutmann et al, 2006). In contrast, Tian et al (2005) reported that only hyperforin and not hypericin (at 0.1 mM, 24 -48 h treatment) caused a time-/dose-dependent induction of Pgp protein by the same cell line.…”
Section: Photochemical Internalisationmentioning
confidence: 95%
“…It is known to be a strong inducer of hepatic and intestinal CYP450 enzymes as well as p-glycoproteins in the intestine through activation of pregnane X receptor (PXR) (4,(18)(19)(20)(21)(24)(25)(26)(27)(28)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). Hyperforin, its most active compound, has also been reported to be a potent activator of pregnane X receptor (PXR) (4,17-19, 40-44,48,51,52).…”
Section: St John's Wort (Sjw) (Hypericum Perforatum)mentioning
confidence: 99%
“…Hyperforin is the most active constituent of SJW, however, it has been demonstrated in many studies that there is great variability in the content of hyperforin among the commercial preparations of SJW, and also that SJW extracts with low hyperforin content (less than 1%) have not demonstrated any clinically relevant interactions (9,51,58,61,63,(65)(66)(67)(68)(69)(70)(71). Gödtel-Armbrust et al (2007) studied the CYP450 induction of LS174T cells by various extracts, commercial products and the purified SJW constituent hyperforin, observing that the content of hyperforin among the commercial preparations of SJW varied 62-fold (range 0.49-30.57 mg/dose) and that the magnitude of the induction correlated statistically significantly with the content of hyperforin in commercial SJW preparations and in dry extracts (69).…”
Section: St John's Wort (Sjw) (Hypericum Perforatum)mentioning
confidence: 99%